Evaluation of the legislative provisions with regard to school discipline in South Africa and determination of whether these provisions provide sufficient guidelines - Mofokeng, Thabo Moses (University of the Free State, 2015)
Abstract not available
Keywords: Dissertation LL.M. (Mercantile Law))--University of the Free State, [2015]; School discipline -- South Africa; School discipline -- Law and legislation -- South Africa; Educational law and legislation -- South Africa